Giant Medial Sphenoid Wing Meningioma with Hyperostosis Sphenoid Bone : A Case Report - Faisal; Hutagalung, Tommy Rizky; Dharmajaya, Ridha (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2020)
Introduction: Meningiomas of the sphenoid wing make up approximately 15–20% of total cranial meningiomas.Giant medial sphenoid involve the dura of the greater and lesser wings of the sphenoid, the anterior clinoid process,the spheno-orbital bone and the middle cranial fossa, hyperostosis bone was common to found. Surgicalmanagement of giant medial sphenoid is extremely challenging due to their intimate relationship with vital neuralstructures.Case Report : A 40-year-old woman came to the emergency room with complaints of decreased consciousness thathad been experienced since 1 week , recurrent headaches, weakness of the right limb and history of blurred vision. Anon-contrast head ct scan and MRI brain contrast revealed an extra-axial giant mass meningioma in left medialsphenoid wing with hyperostosis bone Craniectomy tumor removal was performed with a subtemporal approachcombined with cranio-orbytozygotomy.Discussion : Hyperostosis is a common phenomenon occuring in different meningiomas with incidence rangingfrom 25 to 49% of meningiomas.it is most commonly seen in sphenoid wing and convexity meningioma . The bonyhyperostosis is of neoplastic nature and is responsible for many of the clinical manifestation of such tumors andhence should be totally drilled to achieve cure and avoid recurrence.Conclusion : Sphenoid wing meningioma en plaque, mainly meningothelial meningiomas, are characterized by theassociated bony hyperostosis that gives them a distinct radiological appearance. Extensive tumor removal is crucialfor correction of proptosis and adequate visual decompression to achieve satisfactory cosmetic and functionaloutcome.